2001
DOI: 10.1159/000047074
|View full text |Cite
|
Sign up to set email alerts
|

Can Anesthesiologic Strategies for Caesarean Section Influence Newborn Jaundice?

Abstract: Rationale and Objectives: Neonatal jaundice is a frequent problem in neonatology and can be influenced by many factors. Our study arose from the clinical observation that among all newborns delivered by caesarean section in our center, some had a more intense physiological jaundice. We began by reviewing clinical anesthesiological case-sheets to ascertain whether this difference was linked to the use of different anesthesiologic strategies. We then performed a prospective study on healthy preterm and term newb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…It is expected that anesthetic agents cross the placenta, considering the time from induction of anesthesia to clamping of the umbilical cord. Therefore, it is likely that anesthetic technique can be included among factors with possible influence on neonatal jaundice (7). Recently, Alkan et al showed that bupivacaine did not effect neonatal bilirubin levels and that sevoflurane increased bilirubin levels (8).…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that anesthetic agents cross the placenta, considering the time from induction of anesthesia to clamping of the umbilical cord. Therefore, it is likely that anesthetic technique can be included among factors with possible influence on neonatal jaundice (7). Recently, Alkan et al showed that bupivacaine did not effect neonatal bilirubin levels and that sevoflurane increased bilirubin levels (8).…”
Section: Introductionmentioning
confidence: 99%
“…Hoetzel and Schmidt [16] also reported that not only volatile anesthetics (ISO and sevoflurane) but also other commonly used anesthetics (propofol and opioids) can induce HO-1 expression. Interestingly, De Amici et al [17] performed retrospective and prospective studies of term and preterm newborns delivered by cesarean section and found that some had a more intense physiologic jaundice. They found that total bilirubin levels were higher in infants exposed to ISO (∼2-fold) than in those exposed to sevoflurane 72–120 h after delivery, but they could not draw any definitive conclusions regarding the mechanism(s) involved.…”
Section: Discussionmentioning
confidence: 99%
“…Sezaryen doğum sırasında kullanılan anestezik maddelerin bebekte sarılık oluşumunu kolaylaştırdığı bildirilmiştir (16) .…”
Section: Discussionunclassified